833. Characteristics and Utilization Patterns of Colistin Compared with Newer Agents in Gram-Negative Infections. (31st December 2020) - Marcella, Stephen; Doremus, Casey; Echols, Roger
Abstract: Background: Colistin has resurfaced in light of Gram-negative (GN) resistance. New antibiotics to treat antibiotic resistant GN infections (eg, ceftazidime-avibactam, ceftolozane-tazobactam, meropenem-vaborbactam [new agents]), have recently been approved but their use vs colistin is unclear. We compared the overall use of colistin and new agents from 2014 to 2018 in patient days on therapy (PDOT). Methods: Data on non-cystic fibrosis patients from the Premier Healthcare Database was used. PDOT was tabulated quarterly for Premier hospitals and projected to the US population. A subset of data from 2016 to 2018 with microbiologically confirmed GN (MCGN) infections was selected for adult inpatients receiving ≥3 days of therapy with colistin, new agents, carbapenems, or extended-spectrum cephalosporins. The index infection was defined either as the first carbapenem-resistant (CR) or -sensitive infection if no CR infection occurred. Patients could be treated with ≥1 antibiotic per infection. Utilization was examined by pathogen and patient characteristics. Results: PDOT with colistin decreased from 2015 to 2018, while new agents have increased (Figure). During 2015–2018, colistin and any of 3 new agents were used by 3, 320 and 5, 781 inpatients, respectively, of whom, 649 (20%) and 1, 284 (22%) had MCGN pathogens. Colistin-treated patients were sicker than patients treated with new agents (Table), underlying renal disease was present in 34.5% vs 36.3 %, and median length of stay of 17 vs 15 days, respectively. Mean total hospital cost was $93, 815 vs $84, 013 for colistin and new agents, respectively. Mortality was greater in colistin patients (18% vs 12%; p< 0.0001). CR infections constituted similar proportions of colistin and new agent use (79% vs 75%). Colistin accounted for 15.2% of CR Acinetobacter treatments and 9.7% of CR Enterobacterales (CRE) treatments compared with 4.5% and 12.8%, respectively, for new agents. Figure. Projected Inpatient PDOT Table. Conclusion: Colistin use has decreased simultaneously with the introduction and increased use of new agents in the USA. Colistin was used more frequently in sicker patients and for Acinetobacter spp. infections than for CRE infections. Patients on colistin have worse outcomes, probably due to baseline differences in their health status. Disclosures: Stephen Marcella, MD, Shionogi Inc. (Employee) Casey Doremus, MS, Shionogi Inc. (Employee) Roger Echols, MD, Shionogi Inc. (Consultant)